Unboxing Android USB : a hands-on approach with real world examples - Regupathy, Rajaram (Apress, 2014)
Unboxing Android USB focuses on apps that use USB. This book covers everything starting from simple tasks like managing media with USB to complex tasks like Android ADB and developing application which exploit the potential of USB framework. With use cases that help developers build real world apps in real-time utilizing the advanced features of USB framework Unboxing Android USB tries to cover every single aspect of the app development cycle in totality. Unboxing Android USB helps you learn newly introduced android open accessory protocol with unique examples such as using USB Keyboard with Android device without USB host mode enabled and switching from MTP to MSC. The book is organized based on the USB functions, with each chapter explaining different USB classes available in Android. The functionalities are explained by starting from the USB specification followed by block diagrams that explain different blocks available in that USB class, followed by sequence diagram that elucidates flow of control and data. Each chapter has a unique sample Android application that uses the particular USB function.